Fast microwave calibration system for cryogenic device characterization. (1st November 2022) - Chen, Yong; Duan, Peng; Jia, Zhi-long; Yang, Xin-xin; Zhang, Chi; Kong, Wei-cheng; Li, Hai-Ou; Cao, Gang; Guo, Guo-Ping
Abstract: We designed a calibration system to characterize the performance of microwave devices at low temperatures. This system comprises an in-situ calibration circuit and an adapted thru-reflect-line calibration algorithm, with which we can transfer the reference ports from room temperature to cryogenic temperature with high precision. We validated the circuit and the algorithm at room temperature with better than 0.9 dB accuracy. In addition, we demonstrated how we can extract the actual S 21 of a 20 dB attenuator and a high pass filter at 20 mK using this calibration system. The calibration bandwidth of this system covers from 4.1 GHz to 18 GHz. The requirement that the phase difference between line and thru be greater than 20°determines the lower frequency limit, and the maximum operational frequency of the microwave switch determines the upper frequency limit. This system can be used for fast and accurate analysis of various cryogenic devices such as filters and amplifiers.